(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
Worldwide, the incidence of fetal pathology in pregnant women with urinary tract infections and kidney disease is 1-2%. In some countries, especially in European countries, it is 0.5-1%, and in Asian countries it is 4-6%. It is clear that in Asian countries, the incidence of kidney disease in mothers is higher, which depends on the water they drink, lifestyle, hereditary pathologies and a number of other factors. The urinary organs of fetuses whose mothers had kidney pathologies were compared with those of fetuses whose mothers did not have kidney pathologies in terms of morphometric, histotopographic, and statistical characteristics. For this purpose, the histological, morphometric, histotopographic, histochemical, and statistical aspects of the kidneys, ureters, and bladder were studied in the control group of fetuses without kidney pathologies.